The Impact of Regular Physical Activity on Lipid Profile and Cardiovaskular Health in Adolescents : A Literature Review - Muhammad Al Zaki; Umar Umar; Ronni Yenes; Willadi Rasyid; Yovhandra Ockta; Adri Budiwanto (Postgraduate, University of Mataram, 2023)
This literature review delves into the impact of regular physical activity on lipid profiles and cardiovascular health in adolescents, addressing the growing concern of sedentary lifestyles and unhealthy habits contributing to increased cardiovascular disease risks among teenagers. By systematically searching academic databases and scientific journals using relevant keywords, a selection of 8 articles was chosen for review after rigorous screening and eligibility assessment. The findings of the review underscore the significant relationship between physical activity, metabolic parameters, and cardiovascular risk factors in adolescents. Studies consistently highlight the benefits of regular physical activity in improving lipid profiles, insulin sensitivity, and overall cardiovascular parameters in this population. For instance, adolescents engaging in moderate to high-intensity physical activity demonstrated reduced risks of metabolic syndrome and improved insulin sensitivity. Lifestyle modifications encompassing increased physical activity and dietary changes were associated with positive alterations in lipid and glycemic profiles, particularly in high-risk pediatric individuals. Notably, regular vigorous-intensity physical activity was found to yield favorable cardiometabolic outcomes in adolescents with type 2 diabetes. In conclusion, the review emphasizes the critical role of regular physical activity in maintaining cardiovascular health and managing metabolic risk factors among adolescents. Participation in physical activity, particularly at moderate to high intensity, holds promise for significant improvements in lipid profiles and cardiovascular parameters. These findings underscore the importance of promoting active lifestyles among teenagers to prevent cardiovascular disease and enhance overall health outcomes.